(untitled) (Pedagogy of Higher and Secondary Education, 2007)
Lessons of musical sajatovedenie and their role in formation of professional thinking of the future teachers of music. The lessons of musical sayatovedenie set us the positive pattern of comparative musicology, helping to consider the questions of history of the Ukrainian musical culture under a new point of view - under the comer of comparative analysis, to find out general to conformity to the law of musical-history process on different stages of development of society.